Low intake of essential amino acids and other risk factors of stunting among under-five children in Malang City, East Java, Indonesia - Annisa Rizky Maulidiana; Endang Sutjiati (SAGE Publishing, 2021)
Background: The lack of energy-protein intake has been shown to increase the risk of stunting in under-five children. The quality of protein in food is assessed by the completeness of amino acid content. This study aims to determine the amount of essential amino acid (EAAs) intake and other risk factors of stunting among under-five children. Design and methods: A descriptive, case-control study was performed in the work area of Kedungkandang Health Center Malang. The subjects were 24-59 month-old children with a total of 23 stunted (height-for-age Z-score (HAZ) <-2 SD) and 57 normal children (HAZ ≥-2 SD). Furthermore, the data were collected using anthropometric measurement, validated and pre-tested questionnaires, which were analyzed using multiple logistic regression. Results: The intake of all the nine EAAs in stunted children was lower than that of non-stunted children. However, only histidine, isoleucine, and methionine were significantly different (p<0.05). The significant risk factors of stunting include a family income per month fewer than the Regional Minimum Wages [OR=12.06, 95% CI 1.83-79.53], being underweight [OR=7.11, 95% CI 1.49-33.93], breastfeeding of less than 6 months [OR=5.34, 95% CI 1.28-22.20], and the lack of EAA methionine intake [OR=0.14, 95% CI 0.03-0.67]. Conclusions: Stunted children may not receive sufficient dietary intake of EAAs in their diet. Furthermore, the lack of EAAs intake, especially methionine, alongside low family income, underweight, lack of breastfeeding and variety in food consumption were the risk factors of stunting among under-five children in a selected Health Center in Malang City, Indonesia.